«Faux-Raccords». Due testimoni tardi del «Guiron le Courtois» e i loro raccordi ciclici (Carte Romanze, 2024)
In this paper, we aim to present and comment the peculiar physionomies of Guiron le Courtois’ interstitial narrative in two late testimonies (ms. Torino, Biblioteca Nazionale Universitaria, L.I.7-9 and early printed book Meliadus de Leonnoys, Paris, Galliot du Pré, 1528) tied to the δ1 family, also known as the «vulgate» version, the one that circulated most in France, of this important Arthurian cycle. The paper also contains the first critical edition of a few unpublished excerpts.
Keywords: middle french; cycle; rewriting; arthurian prose romance; interstitial narrative; early printed books